Enhancing Critical Thinking Skills Through the Development of the '4Tif Fun' Model in Social Studies Learning - Faridatul Lailiyah; Halimatur Rizqiyah (Journal of Social Studies Education and Humanities Research, 2024)
Problems in social studies learning are so diverse that realizing students who are skilled in critical thinking can be difficult for teachers in the learning process. Therefore, this research intends to provide innovation in the learning process by developing the 4Tif Fun learning model through a combination of cooperative learning methods, namely make a match and two stay two strays. This research uses a qualitative-descriptive method because it explains in detail the things related to the problems in this research. The research location was at Kanzul Ulum Burneh Junior High School, Bangkalan-Madura. The subjects of this study were class VIII students totaling 32 students. The results of this study indicate that the 4Tif Fun learning model is able to improve students' critical thinking skills, from 35% of students who are able to think critically to 86,12% of students who are able and skilled in critical thinking. The most important thing is that the VIII grade students of Kanzul Ulum Junior High School have realized that learning social studies is important as an asset in carrying out daily life, especially living in society, and caring for the environment, social, and local culture.